Speed sensorless direct torque control of IMs with rotor resistance estimation - Barut, Murat; Bogosyan, Seta; Gokasan, Metin (Elsevier BV, 2005)
Direct torque control (DTC) of induction motors (IMs) requires an accurate knowledge on the amplitude and angular position of the controlled flux in addition to the information related to angular velocity for velocity control applications. However, unknown load torque and uncertainties related to stator/rotor resistances due to operating conditions constitute major challenges for the performance of such systems. The determination of stator resistance can be performed by measurements, but methods must be developed for estimation and identification of rotor resistance and load torque. In this study, an EKF based solution is sought for determination of the rotor resistance and load torque as well as the above mentioned states required for DTC. The EKF algorithm used in conjunction with the speed sensorless DTC is tested under eleven scenarios comprised of various changes made in the velocity reference beside the load torque and rotor resistance values assigned in the model. With no a priori information in the estimated states and parameters, it has been demonstrated that the EKF estimation and sensorless DTC perform quite well in spite of the uncertainties and variations imposed on the system.